Synthesis, characterization and thermal behaviour of solid state compounds of 4-methoxybenzoate with Manganese, Nickel and Copper - Rodrigues, Emanuel Carlos; Vallejo, Adriana Cossu; Ionashiro, Elias Yuki; Bannach, Girbert; Ionashiro, Massao (Eclética Química, 2005)
Solid state M-L compounds, where M stands for bivalent Mn, Ni, Cu and L is 4-methoxybenzoate, have been synthesized. Simultaneous thermogravimetry – differential thermal analysis (TG-DTA), X-ray powder diffractometry, infrared spectroscopy, elemental analysis and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results led to information about the composition, dehydration, thermal stability and thermal decomposition of the isolated compounds.